The Antityrosinase Activity of Mitragyna speciosa Korth Leaf Ethanolic Extract - Normaidah, Normaidah; Rahmah, Maslia; Izma, Hayatun; Fadlilaturrahmah, Fadlilaturrahmah; Sari, Anna Khumaira (Jurnal Ilmiah Kesehatan (JIKA), 2024)
The kratom plant (Mitragyna speciosa Korth) is a the plant that is traditionally used to soften the skin. Kratom leaves have very strong antioxidant activity so they are predicted also to have anti-tyrosinase activity. The potential inhibition of tyrosinase enzyme activity is thought to come from the content of flavonoid compounds, polyphenols, steroids, tannins, and quinones. This research aims to determine the tyrosinase inhibitory activity of ethanol extract of M. speciosa leaves. The inhibitory activity of the tyrosinase enzyme using L-DOPA as substrate and kojic acid as positive control. Antityrosinase testing was carried out by in vitro method using UV-vis spectrophotometer through determination of IC50 value. The results of the antityrosinase activity test of ethanol extract of M. speciosa leaves showed an IC50 value of 2117.708 ppm. The ethanol extract of M. speciosa leaves is scientifically proven to have antityrosinase activity with a weak category.